A Microbiological, Toxicological, and Biochemical Study of the Effects of Fucoxanthin, a Marine Carotenoid, on Mycobacterium Tuberculosis and the Enzymes Implicated in Its Cell Wall: A Link Between Mycobacterial Infection and Autoimmune Diseases - Echeverria-Morgado, J (Multidisciplinary Digital Publishing Institute (MDPI), 2019)
This study explored the antitubercular properties of fucoxanthin, a marine carotenoid, against clinical isolates of Mycobacterium tuberculosis (Mtb). Two vital enzymes involved in Mtb cell wall biosynthesis, UDP-galactopyranose mutase (UGM) and arylamine-N-acetyltransferase (TBNAT), were selected as drug targets to reveal the mechanism underlying the antitubercular effect of fucoxanthin. The obtained results showed that fucoxanthin showed a clear bacteriostatic action against the all Mtb strains tested, with minimum inhibitory concentrations (MIC) ranging from 2.8 to 4.1 μM, along with a good degree of selectivity index (ranging from 6.1 to 8.9) based on cellular toxicity evaluation compared with standard drug isoniazid (INH). The potent inhibitory actions of fucoxanthin and standard uridine-5 -diphosphate against UGM were recorded to be 98.2% and 99.2%, respectively. TBNAT was potently inactivated by fucoxanthin (half maximal inhibitory concentration (IC50) = 4.8 μM; 99.1% inhibition) as compared to INH (IC50 = 5.9 μM; 97.4% inhibition). Further, molecular docking approaches were achieved to endorse and rationalize the biological findings along with envisaging structure-activity relationships. Since the clinical evidence of the last decade has confirmed the correlation between bacterial infections and autoimmune diseases, in this study we have discussed the linkage between infection with Mtb and autoimmune diseases based on previous clinical observations and animal studies. In conclusion, we propose that fucoxanthin could demonstrate great therapeutic value for the treatment of tuberculosis by acting on multiple targets through a bacteriostatic effect as well as by inhibiting UGM and TBNAT. Such outcomes may lead to avoiding or decreasing the susceptibility to autoimmune diseases associated with Mtb infection in a genetically susceptible host. © 2019 by the authors.